2013
DOI: 10.5154/r.rchscfa.2012.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Producción De Hojarasca Y Retorno De Nutrientes Vía Fliar en Un Matorral Desértico Micrófilo en El Noreste De México

Abstract: La caída de hojarasca y el contenido de macro (Ca, N, P, Mg y K) y microminerales (Fe, Mn y Zn) de las hojas se compararon en dos sitios durante 12 meses (septiembre 2008-agosto 2009). El sitio 1 se ubicó en la comunidad El Llano de La Soledad, Galeana, Nuevo León (1,863 m) y el sitio 2 en la comunidad San José del Alamito, Satillo, Coahuila (1,895 m). En cada sitio se colocaron, aleatoriamente, 10 canastas (1 m2) para la captura de hojarasca. La caída anual de hojarasca en el sitio 2 fue mayor (407 g·m-2·año-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
0
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
4
0
0
1
Order By: Relevance
“…A similar trend was observed for twigs and reproductive structures; in contrast, miscellaneous depositions were higher at the Pinus forest plant community (Table 2). These observations are similar to litterfall values previously reported in studies conducted in the same region (López-Hernández et al, 2013) and in the microphyllous desert scrubland at northeastern Mexico (González-Rodríguez et al, 2013); however, lower quantities (202.7 g m -2 year -1 , 100.2 g m -2 year -1 and 35.2 g m -2 year -1 ) were recorded by Martínez-Yrizar, Nuñez, Miranda, and Búrquez (1999) in the Sonora Desert vegetation of northern Mexico. In this study, leaves represented the major component of litterfall; 66% to 72%.…”
Section: Discussion Litterfallsupporting
confidence: 91%
See 3 more Smart Citations
“…A similar trend was observed for twigs and reproductive structures; in contrast, miscellaneous depositions were higher at the Pinus forest plant community (Table 2). These observations are similar to litterfall values previously reported in studies conducted in the same region (López-Hernández et al, 2013) and in the microphyllous desert scrubland at northeastern Mexico (González-Rodríguez et al, 2013); however, lower quantities (202.7 g m -2 year -1 , 100.2 g m -2 year -1 and 35.2 g m -2 year -1 ) were recorded by Martínez-Yrizar, Nuñez, Miranda, and Búrquez (1999) in the Sonora Desert vegetation of northern Mexico. In this study, leaves represented the major component of litterfall; 66% to 72%.…”
Section: Discussion Litterfallsupporting
confidence: 91%
“…In this study, leaves represented the major component of litterfall; 66% to 72%. These percentages are within the ranges reported by González-Rodríguez et al (2011), González-Rodríguez et al (2013) and López-Hernández et al (2015) for these ecosystems. Santa-Regina (2000), Santa-Regina and Tarazona (2001) and Caritat, García, Lapeña, and Vilar (2006) reported that the leaf component represented 50% to 80% of all litterfall in pine and pine-oak forests.…”
Section: Discussion Litterfallsupporting
confidence: 90%
See 2 more Smart Citations
“…Wilson y Thompson (2005) mencionan que la principal fuente de nitrógeno en estos paisajes está dada por las relaciones simbióticas con bacterias f ijadoras de nitrógeno en los mezquites, además del aporte signif icativo que las hojas en descomposición pueden acarrear al suelo. En este estudio los valores bajos de nitrógeno y fósforo pueden estar relacionados con los valores altos del pH, dando como resultado una baja disponibilidad (Dragovic et al, 2008); González-Rodríguez et al (2013) reportaron valores similares en el pH del suelo en dos sitios de estudio en el Noroeste de México (Nuevo León y Coahuila), mencionan que esta variable tiende a limitar la solubilidad de macro y micro nutrientes en el suelo, siendo los macronutrientes nitrógeno y fósforo los más afectados.…”
Section: Caracterización Del Suelo Por Comunidad Vegetalunclassified